Africa watch - André-Michel Essoungou (Africa Renewal, 2013)
Five months after United Nations Secretary-General Ban Ki-moon and World Bank President Jim Yong Kim visited Africa’s Great Lakes region, a 15-member delegation of the UN Security Council followed suit. The delegation travelled to the region from 4 to 8 October and met with political leaders and local activists, displaced persons and refugees, as well as UN peacekeepers and diplomats.